58: Gendered policy responses to the COVID-19 pandemic - Ceron, Matilde (Edward Elgar Publishing, 2026)
The COVID-19 pandemic was a crisis that disproportionately impacted women, exacerbating pre-existing inequalities and leading to what has been termed a “she-cession.” Early pandemic responses largely failed to incorporate a gender-sensitive approach. In parallel, the crisis revealed structural weaknesses in care policies, women's labour market participation, and their representation in pandemic decision-making. This entry discusses how containment measures, social policies, and economic recovery plans affected gender equality in the EU. It highlights both the limitations of gender-blind responses and the role of feminist advocacy in securing gender mainstreaming provisions in crisis response policies such as the Recovery and Resilience Facility. The discussion underscores the shortcomings of crisis policymaking in addressing structural inequalities and the role of substantive representation in shaping more inclusive policy responses. Future research directions include assessing the long-term labour market effects, deepening intersectional analyses, and improving comparative policy studies on gender-responsive crisis management.